A critical investigation of the problems of teaching poetry to English-speaking pupils in South African senior schools - Durham, Ken (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1969)
This thesis is a study of the problems of teaching poetry to English speaking pupils at South African senior schools. It is a study of what is generally agreed to be 'a peculiarly difficult department of teaching' Reeves 1958. Some would go as far as to suggest that the teaching of poetry is the most difficult aspect of any school subject : "No topic in the school curriculum has so many pitfalls as the teaching of poetry in the classroom: it is easier to go astray in attempting to promote aesthetic responses to a poem than in any other kind of lesson. 'Currey {19S8) p. 126.' If one may judge too by the number of complaints from a large body of teachers (see Chapter Four) about the difficulty of teaching poetry successfully the assessments given by Reeves and Currey appear to be well- founded. Additional weight is given by some of the attitudes of pupils themselves towards poetry and the poetry lesson (see Chapter Three). Further confirmation is evident at Teachers' Conferences and from examiners' reports that examination questions on poetry are often among the most badly answered and the least popular of all questions set. Even more significant, perhaps. were the responses from two separate graduate student teacher groups (U.E.D. English Method classes, Rhodes University 1965, 1967). When asked at the beginning of the course to name the one type of English lesson they felt least confident in handling, 42 of the 64 student teachers answered, 'The poetry lesson'. Into. p. 1.
Keywords: Poetry -- Study and teaching (Secondary) -- South Africa